Clinical impact of concurrent autologous adoptive T cells immunotherapy in active COVID-19 infected cancer patients for chemotherapy - Congcong Li; Dazhao Xu; Linyao Lu; Shu Peng; Haiyang Zhao; Chuxiong Zeng; Lina Hu; Xianzhi Guo; Li Liu; Feifei Huo; Xiumei Rong; Zhenying Geng; et al. (Infectious Agents and Cancer)
Abstract Background The concurrent presence of COVID-19 infection in advanced cancer patients has increased the mortality since the compromised immunity was inevitably worsen. The role and clinical impact of autologous adoptive T cell immunotherapy (ACT) designed for anti-cancer treatment were not known in such circumstances. The safety and potential immune reconstitution of concurrent ACT in advanced cancer patients with active COVID-19 infection have yet unknown as well. The effect of infused ACT on the symptom severity manifestation should be summarized. Methods In this respectively clinical observation study, patients were non-randomized enrolled from the two centers according to the regular therapeutic plans including stage IV cancer patients for scheduled ACT, chemotherapy, cancer patients with symptomatic COVID-19 but without ACT, neither cancer or non-ACT but symptomatic cases of COVID-19 infection. We have incorporated the age-adjusted Charlson comorbidity index (aCCI) for each patient to compare the prognosis of the three groups. All patients were planned for the scheduled standard anti-cancer therapeutic considerations, chemotherapy plus ACT as planned as well as the supportive care.The clinical efficacy and impact of ACT on cancer patients within the 3 months from the peripheral blood apheresis, dendritic cell (DC) and cytokine induced killer T cell (CIK-T ) infusion and subsequent co-existence of COVID-19 infection were recorded as the primary objective. During the same period, the cancer cases without ACT and others were collected to compare the occurrence of both severe and death rate respectively. Results There were 123 patients (35 of ACT, 23 of non-ACT, 65 of non-cancer) with similar aCCI. There were similar cohort-level COVID-19 in-hospital case fatality rates consistent with previously reported data for non-cancer (26.2%, 17/65) and non-ACT cancer (52.2%, 12/23) among those admitted severe cases after the adjustment.There were little overlapped adverse reactions during the ACT therapeutic period even in the presence of active COVID-19 infection. No death case was occurred (0/35) when those exposed to ACT regimen. Cancer patients receiving ACT had a shorter mean time to alleviation of symptoms compared with non-ACT and non-cancer (4.46 versus 16.88 and 17.90 days respectively) as well as the lowered severity incidence of symptoms (P = 0.0010). The infused ACT has not significant impact on peripheral blood count whereas the amount of CD3−CD16+CD56+ NK cells increased (P = 0.0017). The quantity of infused ACT was favorable for augmentation of possibility of severe to mild symptom shift. Conclusions These data demonstrate the clinical safety profiles while ACT infusions with active COVID-19 infection.The intervention of ACT for cancer patients could generate the benefit for symptom alleviation with improved recovery time. The concurrent ACT for advanced cancer patients during such infectious pandemic might simultaneously leverage and reduce the risk of immune compromised situation for subsequent chemotherapy complications.